2014
DOI: 10.1007/s00428-014-1657-8
|View full text |Cite
|
Sign up to set email alerts
|

Acinar cell carcinomas of the pancreas: a molecular analysis in a series of 57 cases

Abstract: Pancreatic acinar cell carcinomas (PACs) are rare but are distinct aggressive neoplasms that phenotypically differ from pancreatic ductal adenocarcinomas (PDACs) and pancreatic neuroendocrine neoplasms (PNENs). Despite recent work on the genetic changes of PACs, their molecular pathogenesis is still poorly understood. In this study, we focus on a comparative genomic hybridization analysis. Based on frequent chromosomal imbalances, the involvement of DCC and c-MYC in the pathogenesis of PACs is further investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 73 publications
5
69
0
Order By: Relevance
“…Mutational analysis of EGFR (exons 18–21) has been investigated recently in 57 ACCs and no mutations have been found (48). In the same study, EGFR immunoreactivity at the cell membrane level was observed in 19/45 (42%) cases.…”
Section: Acinar Cell Carcinoma In Adultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mutational analysis of EGFR (exons 18–21) has been investigated recently in 57 ACCs and no mutations have been found (48). In the same study, EGFR immunoreactivity at the cell membrane level was observed in 19/45 (42%) cases.…”
Section: Acinar Cell Carcinoma In Adultsmentioning
confidence: 99%
“…BRAF mutations have been investigated in only two studies using either whole-exome sequencing analysis (47) or immunohistochemistry with the anti-BRAF V600E antibody (48). BRAF mutations were found in two mixed acinar-ductal carcinomas and in only 1 out of 17 pure ACCs (47).…”
Section: Acinar Cell Carcinoma In Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MYCN is also deregulated in many tumors of neuroectodermal origin [9]. In pancreatic neuroendocrine tumors (PanNET) the role of MYC proteins is largely unknown, although c-MYC has been suggested to act as an oncogene in a fraction of acinar cell carcinomas [10] and ductal adenocarcinomas [11]. PanNETs, which synthesize and secrete hormones, are hormonally syndromic or non-syndromic.…”
Section: Introductionmentioning
confidence: 99%